Integrated Simulation Process Chain: From 3D Roll Forming Design to Crash Analysis - Sedlmaier Albert; Dietl Thomas; Abee André; Harrasser Johann; Pereira Miguel Sousa (MATEC Web of Conferences)
This paper presents an innovative numerical simulation process chain for sheet metal profiles, addressing the full workflow from tooling design and 3D roll forming process simulation to crash simulation. The process begins with defining the bending sequence and the corresponding tooling, tailored to the specifications of a 3D roll forming line. A dedicated preprocessor creates “ready-to-run” finite element models, ensuring an accurate representation of the complex deformation behaviour. Those models include the meshing and material description of the blank and the kinematics used in the process. The simulation employs hexahedral elements, suitable to capture the material flow, strain distribution, contact interactions and workpiece geometry during forming and after springback. To bridge the gap between forming simulations and downstream structural analysis, the roll forming results are mapped onto shell elements commonly used in crashworthiness simulations. A specialized algorithm allows for this transformation, preserving deformation history and enabling the seamless integration of roll forming data into downstream structural analysis. The use of roll forming simulation data in subsequent structural analysis has a significant impact in the quality of those analysis. This holistic approach enhances the fidelity of product performance predictions, offering a robust framework for optimizing forming processes and end-use structural integrity.